OP0175 The eurofever registry for autoinflammatory disease: Update on enrollment after 2 years. (23rd January 2014) - Naselli, A.; Frenkel, J.; Ozen, S.; Konè-Paut, I.; Lachmann, H.; Woo, P.; De Benedetti, F.; Hofer, M.; Neven, B.; Dolezalova, P.; Kümmerle-Deschner, J.; Hentgen, V.; et al.
Abstract : Background: The main limitation to a better knowledge of Autoinflammatory diseases is related to the extreme fragmentation of the diagnosed cases that are spread over different centers and countries. The general aim of the Eurofever Project (agreement n 2007332, EAHC) is to build an international registry on Autoinflammatory diseases. Objectives: To evaluate the number of patients enrolled in the Registry in the first 24 months after starting the enrolment. Methods: A web-based registry collecting baseline and clinical information on Autoinflammatory diseases is available in the member area of the PRINTO web-site. The following monogenic autoinflammatory diseases were considered: FMF, CAPS, TRAPS, mevalonate kinase deficiency (MKD), Blau's syndrome, PAPA, DIRA, NLRP12-mediated periodic fever. Information on CRMO, Behcet's disease, PFAPA and undefined periodic fevers were also collected. Results: During the first 24 months from the beginning of the enrolment 2293 patients from 51 centers in 38 countries have been entered in the registry. At present baseline demographic information from 2293 (M:F=1121:1172) patients are available. In 1797 (78%) complete information on clinical manifestations form disease onset to diagnosis and response to treatment is also available. For each disease the number of enrolled patients is: FMF 694 pts (493 with complete clinical data); TRAPS 215 pts (180 with with complete clinical data); CAPS 180 pts (155 with complete clinical data); MKD 129 pts (107 with complete clinical data); Blau's disease 30 pts (18 with complete clinical data); PAPA 8 pts (all with complete clinical data); NLRP-12 mediated periodic fever 6 pts – 4 with complete clinical data); DIRA 3 pts (all with complete clinical data). In total 19 new mutations have been reported in 22 pts. Among multifactorial autoinflammatory diseases: PFAPA 405 pts (264 with complete clinical data); CRMO 372 pts (334 with complete clinical data); pediatric Bechet disease 79 pts (64 with complete clinical data) and 173 patients with undefined periodic fever (167 with complete clinical data). Conclusions: A common registry for collection of patients with Autoinflammatory disease is available and the enrolment is ongoing. The analysis of data on the clinical presentation, outcome and response to treatment of Autoinflammatory diseases and comparative studies among different Autoinflammatory conditions are ongoing. Disclosure of Interest: None Declared